Nation against nation / Thomas M. Franck - Franck, Thomas M. (1985)
Happy and misleading Auguties, et tú, nehru, rather good document, the end of innocence, his sissters and his cousins and his aunts, the United Nacions civil servece, the secretaruy-general invents himself, tilling the void, action by la secretary general in the face of inaction by everyone else, the security council in search of a arole, the general assembly and the U. s. national interest, place where lies are told.